Model Perencanaan Strategi Bisnis Dan Teknologi Informasi Pada Perusahaan Penyewaan Vcd/Dvd - Pangestu, Harijanto (ComTech: Computer, Mathematics and Engineering Applications, 2010)
In a tighter business competition, company in original VCD/DVD rental needs strategic planning system and information technology to win the competition. In order to fulfill the information, the company is doing the system analysis and information technology, and also suggesting a plan to system developing and company’s information technology. The research method is doing literature study, field research, and analysis method and system planning and strategic information technology based on the method by Tozer. The expected result is through strategic system planning and information technology, the company could choose the exact strategy in solving internal problems.